Ring-Opening Polymerization of Cyclic Ester Monomers by Poly(propylene glycol) in the Presence of Monomer Activator and Examination of Triblock Copolymer Solution Properties - Il Kim, Jae; Ju Kang, Hwi; Yeon Kwon, Doo; Lee, Bong; Jae Chun, Heung; Ho Kim, Jae; Suk Kim, Moon (Current Nanoscience, 2011)
The ring-opening polymerization of ε-caprolactone (CL), δ-valerolactone (VL), and trimethylene carbonate (TMC) was carried out with polypropylene glycol (PPG) as an initiator in the presence of the monomer activator HCl to synthesize various polyesterpoly( propylene glycol)-polyester triblock copolymers (polyester-PPG-polyester). The resultant polyester-PPG-polyester triblock copolymers had molecular weights close to theoretical values. The formation of polymeric micelles from these triblock copolymers in aqueous media was confirmed by NMR, dynamic light scattering, and fluorescence techniques. The critical micelle concentrations (CMC) of the polyester-PPG-polyester triblock copolymers ranged from 1.7 x 10-3 to 2.1 x 10-3 mg/mL. The partition equilibrium constants illustrated the hydrophobicities of the polyester cores of the polyester-PPG-polyester triblock copolymers. In conclusion, we confirmed that the polyester-PPG-polyester triblock copolymers formed micelles and hence may be potential hydrophobic drug carriers.
Keywords: micelle